Analisis Hukum Online Dispute Resolution dalam Penyelesaian Sengketa Non-Litigasi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Article 1 point 10 of Law Number 30 of 1999 concerning alternative dispute resolution, is a form of dispute resolution outside the court, including mediation. Alternative dispute resolution, the parties are assisted by a third party in resolving the dispute with a mediator. The alternative dispute resolution law provides a variety of non-litigation dispute resolution options. It should be emphasized that the option of dispute resolution with alternative dispute resolution is limited to disputes in the civil field. The purpose of this study is to determine the application of mediation through online dispute resolution in Indonesian laws and regulations as well as to find out the obstacles and challenges in the implementation of online dispute resolution mediation in an effort to resolve disputes in a non-litigation manner. The research method used is using the empirical juridical approach method, the research specification used in this study is descriptive analytical. The type of data in this study uses qualitative data while the data source uses primary data, namely interviews, observations, and secondary data, namely by studying the provisions of laws and regulations, other regulations, researching principles, conceptions, views, doctrines, and legal rules through books, journals, papers, and research results, the results of data analysis to answer problem issues. Conclusion The application of mediation through Online Dispute Resoution in laws and regulations in Indonesia is regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. Article 5 paragraph (3) of PERMA Number 1 of 2016 concerning Mediation Procedures in Court. The obstacles to the implementation of Online Dispute Resolution depend on the good faith of the parties and the equipment used. Mediation is difficult to reach an agreement if the parties do not provide information clearly and transparently, and are constrained by the equipment used.